2017
DOI: 10.1177/0363546517691961
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Predict Failure in Anatomic Single-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: Meniscal deficiency is the most significant factor to predict graft failure in single-bundle anatomic ACL reconstruction. Shallow nonanatomic femoral tunnel positioning and younger patient age are additional risk factors for failure, but their relative importance is less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 60 publications
2
89
1
1
Order By: Relevance
“…10,11 Meniscal deficiency has been reported as the most significant factor to predict graft failure after ACLR. 16 The posterior horn of the medial meniscus is a known secondary stabilizer to anterior tibial translation and thus may help stabilize the ACL-deficient knee. 15,19 In contrast, when the ACL is torn in combination with a meniscus ramp lesion, anterior knee translation may increase.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Meniscal deficiency has been reported as the most significant factor to predict graft failure after ACLR. 16 The posterior horn of the medial meniscus is a known secondary stabilizer to anterior tibial translation and thus may help stabilize the ACL-deficient knee. 15,19 In contrast, when the ACL is torn in combination with a meniscus ramp lesion, anterior knee translation may increase.…”
Section: Discussionmentioning
confidence: 99%
“…ACL reconstruction failure has been found to be related to patient age, sex, body mass index, time from surgery, graft size, meniscal integrity, tibial tunnel malposition and early return to sport [23,[26][27][28][29][30]. Parkinson et al [31] found that meniscal integrity was the strongest predictor of ACL reconstruction failure. Increased graft laxity was found in ACL reconstruction patients with medial meniscal deficiency [32], and a higher incidence of a residual pivot shift was reported in meniscal-deficient knees [33].…”
Section: Late Post-operative Complicationsmentioning
confidence: 99%
“…Increased graft laxity was found in ACL reconstruction patients with medial meniscal deficiency [32], and a higher incidence of a residual pivot shift was reported in meniscal-deficient knees [33]. Greater stress through the ACL graft in meniscal-deficient knees may explain a higher graft failure rate [31]. Strength testing should be conducted throughout recovery to assess progress and to determine if milestones are met for advancement of function.…”
Section: Late Post-operative Complicationsmentioning
confidence: 99%
“…It is now accepted that ACL reconstruction should be advocated in the young, even before skeletal maturity, and anatomic transphyseal ACL reconstruction can be safely performed to restore functional stability 19,26 . After ACL reconstruction, there is considerable recent evidence that 2 nd ACL injuries occur more frequently in the young 1,21,29,34,37,52 .…”
Section: Introductionmentioning
confidence: 99%